1994
DOI: 10.1159/000126719
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Progestin Receptors in Raphe Neurons of Steroid-Treated Monkeys

Abstract: Progesterone increases prolactin secretion in estrogen-primed primates. This action is probably mediated through a neural mechanism since lactotropes do not have progestin receptors (PR). This laboratory recently reported localization of PR in serotonin neurons of female macaques. Since serotonin (5HT) is a putative prolactin stimulatory agent, it was of interest to examine the regulation of PR in this neural system. Spayed monkeys were treated with either (1) an empty silastic capsule; (2) an estrogen (E)-fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
2
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 33 publications
5
60
2
2
Order By: Relevance
“…Both estrogen and progesterone receptors are located in this nucleus in the rat (Alves et al, 1998). In addition, estrogen induces progesterone receptor expression in the dorsal raphe nucleus (Bethea, 1994). Previous studies have suggested that estrogen reduces 5-HT 1A receptor gene expression and the addition of progesterone enhances this effect on 5-HT 1A autoreceptors (Pecins- Thompson and Bethea, 1999) but reverses the effect of estrogen on the postsynaptic 5-HT 1A receptors (Birzniece et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Both estrogen and progesterone receptors are located in this nucleus in the rat (Alves et al, 1998). In addition, estrogen induces progesterone receptor expression in the dorsal raphe nucleus (Bethea, 1994). Previous studies have suggested that estrogen reduces 5-HT 1A receptor gene expression and the addition of progesterone enhances this effect on 5-HT 1A autoreceptors (Pecins- Thompson and Bethea, 1999) but reverses the effect of estrogen on the postsynaptic 5-HT 1A receptors (Birzniece et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…We showed that serotonin neurons in monkeys express the nuclear form of the progestin receptor (Bethea, 1993;1994) and this receptor is markedly induced in animals treated with estrogen for several weeks. We previously showed that the mixed progestin receptor antagonist RU486 blocked P-induced prolactin secretion (Pecins-Thompson and Bethea, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This laboratory has shown that HT increases tryptophan hydroxylase production in the dorsal raphe nucleus Sanchez et al, 2005) and serotonin release in the hypothalamus (Centeno et al, 2007). Serotonin neurons express ERb and PR for mediation of the action of ovarian hormones (Bethea, 1993(Bethea, , 1994Gundlah et al, 2000Gundlah et al, , 2001. Thus, serotonin innervation of the PVN could mediate the decrease in CRH expression, but either an inhibitory serotonin receptor is required or more likely, an inhibitory GABA interneuron is present.…”
Section: Discussionmentioning
confidence: 99%